Implementasi Kualitas Pelayanan, Kelengkapan Produk dan Harga Produk Terhadap Kepuasan Konsumen di Swalayan XYZ - Tiara Kartika Sari; Khabib Alia Akhmad; Esti Dwi Rahmawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The increasing growth of the industry now can cause competition in companies, one of which is the retail business. Where must be able to compete competitively to understand consumers. Companies need to implement more rigorous and innovative strategies in developing businesses, so as to meet the satisfaction of consumers. This study aims to determine the effect of service quality, product completeness, and product prices on customer satisfaction at Swalayan xyz. This study uses quantitative methods, and sampling is a non-probability sampling technique with purposive sampling type where sampling is done using certain considerations. The sample taken was 100 respondents. The study used multiple liner regression analysis techniques and hypothesis testing which were analyzed using SPSS 25 software. This study has independent variables and dependent variables. Where the independent variable is Service Quality (X1), Product Completeness (X2), and Product Price (X3), for the dependent variable, namely Customer Satisfaction (Y). The results showed that (1) Service Quality has a positive and significant effect on Customer Satisfaction. (2) Product Completeness has a positive and significant effect on Customer Satisfaction. (3) Product Price has a positive and significant effect on Customer Satisfaction. (4) Service Quality, Product Completeness, and Product Price simultaneously have a positive and significant effect on Consumer Satisfaction.